Hubungan Pengetahuan Tentang Anemia, Frekuensi Konsumsi Protein, Pangan Sumber Fe, dan Tanin dengan Gejala Anemia Pada Remaja Putri Di SMA YPHB Kota Bogor Tahun 2020 - Dinda Annisa Fitri (2021)
Adolescent girls are one of the vulnerable groups to suffer from anemia. Factors that can influence anemia in adolescent girls are knowledge of anemia, frequency of protein consumption, food sources of Fe, and tannins. The purpose of this study was to determine and analyze the relationship between knowledge about anemia, frequency of protein consumption, food sources of Fe, and tannins with symptoms of anemia in adolescent girls at SMA YPHB Bogor City in 2020. This study used a cross sectional study design. The sampling method used was non-probability sampling, namely purposive sampling. Subjects in this study were adolescent girls aged 15-18 years, as many as 53 adolescent girls. Data on anemia symptom status and knowledge about anemia were taken using a questionnaire distributed online, namely Google Form. Data on the frequency of protein consumption, food sources of Fe, and tannins were obtained through online interviews using the Food Frequency Questionnaire (FFQ). The results of bivariate analysis using the chi-square test showed a relationship between knowledge of anemia (p = 0.020), frequency of protein consumption (p = 0.004), food sources of Fe (p = 0.008), and tannins (p = 0.009) with symptoms of anemia. This shows that there is a relationship between knowledge about anemia, the frequency of protein consumption, food sources of Fe, and tannins with symptoms of anemia in adolescent girls at SMA YPHB Bogor City in 2020.